MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Rizal, Muhammad; Efendi, Ramdan (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This community service aims to design appropriate sharia microfinance institutions in Gunung Bunder II Village, Pamijahan District, Bogor Regency. The subject of this community service is the people of Gunung Bunder II Village, Pamijahan District, Bogor Regency, West Java Province. In this community service, activities are carried out based on the Participatory Action Research (PAR) method. The result of this community service is that an appropriate sharia microfinance institution design will be formed by involving the Gunung Bunder II Village and the Faculty of Islamic Economics and Business, Sahid Bogor Islamic Institute, then a process of socialization, training, selection of sharia microfinance institution models and product and service development in designing sharia microfinance. With this community service, it can be concluded that this activity aims to provide education and make it easier for people to access financial institutions and so that people start switching to sharia finance in their daily lives.